Economic analysis in health care - Morris, Stephen
"Economic Analysis in Health Care is intended as a core textbook for advanced undergraduate and postgraduate students of health economics. The authors provide comprehensive coverage of the field of economics in health care systems and the evaluation of health care technologies."--BOOK JACKET.